2017
DOI: 10.4103/2279-042x.200983
|View full text |Cite
|
Sign up to set email alerts
|

Cytopenia occurrence in kidney transplant recipients within early post-transplant period

Abstract: Objective:This study assessed incidence, severity, and time to occurrence of drug-induced leukopenia/thrombocytopenia within 1st month after kidney transplantation.Methods:This cross-sectional study was conducted on newly kidney transplant recipients from two hospitals, Iran. Patients with thrombocytopenia due to acute antibody-mediated rejection were excluded from the study. Demographic, clinical, and laboratory data of patients within the 1st month after transplantation were collected.Findings:Of 213 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A delicate balance is needed to prevent rejection and avoid various complications including cytopenia. Cytopenia is common in kidney transplant recipients [ 1 ]. Twenty to sixty % of KTR will have one episode of either neutropenia or cytopenia during the course of their transplant [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A delicate balance is needed to prevent rejection and avoid various complications including cytopenia. Cytopenia is common in kidney transplant recipients [ 1 ]. Twenty to sixty % of KTR will have one episode of either neutropenia or cytopenia during the course of their transplant [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cytopenia is part of the numerous complications occurring post-transplantation and is known to complicate treatment administration in up to 60% of KTR who will experience at least one episode of leucopenia or neutropenia [ 25 ]. A meta-analysis found that VGC 900 mg daily was associated with a 3.3 times greater risk of leucopenia [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated incidence of leukopenia in kidney transplant patients ranges from 10-55%. 9 There is also a high rate of thrombocytopenia following renal transplantation in the first year, with the majority of recipients experiencing the lowest platelet counts within the first three months after the transplant 10 which causes an oxygen deficit and immune system dysfunction that have a broad impact on the body. 11 Post-transplant erythrocytosis is usually observed in 10-15% of patients 12 and is typically evident within the first year of transplant.…”
Section: Discussionmentioning
confidence: 99%